2021
DOI: 10.3390/ani11020335
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Horsetail (Equisetum arvense) and Spirulina (Spirulina platensis) Dietary Supplementation on Laying Hens Productivity and Oxidative Status

Abstract: The purpose of this study was to examine the effect of dietary horsetail (Equisetum arvense) and spirulina (Spirulina platensis) supplementation on performance, egg quality, serum biochemical and antioxidant status of laying hens. A total of 648, 63-week-old Hy-Line W-36 layers were divided into nine groups with eight replicates per group (nine birds per replicate). A feeding trial was conducted under completely randomized design with factorial arrangement 3 × 3 consisting of three different dietary levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Egg weight was not significantly affected by the dietary inclusion of 1% or 3% spirulina for 15 days of supplementation. Other investigations using doses of 1-2% for a longer period (12 weeks) did not find changes in this parameter [12]. Omri et al [7] reported that doses of 1.5% and at least 6 weeks were necessary for changes in egg weight to be observed.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Egg weight was not significantly affected by the dietary inclusion of 1% or 3% spirulina for 15 days of supplementation. Other investigations using doses of 1-2% for a longer period (12 weeks) did not find changes in this parameter [12]. Omri et al [7] reported that doses of 1.5% and at least 6 weeks were necessary for changes in egg weight to be observed.…”
Section: Discussionmentioning
confidence: 89%
“…These authors also found changes in color after 4-5 days of supplementation. Other authors [12] also found that the yolk color score improved from 1% doses, although these authors fed hens for a longer period of 12 weeks. Other research using a shorter period (6 weeks) [42] found that differences were not marked between 2 and 2.5% supplementation, with yolks having a pleasing color with 2% supplementation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Indeed, the prohibition of using AGP can implicate negative effects on broiler production and health (Sugiharto, 2016;Sugiharto & Ranjitkar, 2019). Various attempts have been conducted to find alternatives to AGP (Cimrin et al, 2020;Tufarelli et al, 2021). In this regard, herbal plants are being used as feed additives as part of the initiative to replace AGP for broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Blood biochemical parameters had been used as metabolic variables to assess the welfare of poultry [ 12 ]. The behavior, blood corticosterone and blood biochemical parameters in laying hens change during the stress [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%